The diagrammatic method of Berezinskii for one-dimensional disordered wire with spin-orbit interaction - Suleymanli, Bahruz; Nakhmedov, Enver; Tatardar, Farida; Tanatar, Bilal (ELSEVIER, 2023)
We extend Berezinskii's diagram technique to the one-dimensional disordered wire containing Rashba and Dresselhaus spin-orbit interactions. The retarded and advanced Green's functions are factorized in coordinates space in the presence of spin-orbit interactions. This factorization allows us to transform all coordinate dependence of the Green's functions from lines to the impurity vertices. Our calculations show that all possible impurity vertices giving a contribution to the correlators do not differ from those given in the conventional technique, except that they are written in a 2 x 2 matrix form and the Fermi velocity r iota*F now depends on the spin-orbit coupling constants. The diagrammatic method of Berezinskii with spin-orbit interaction is used to obtain the distribution of the electron density of the localized state p infinity(y).
Keywords: White-noise Gaussian random potential; Spin-orbit interaction; Electron density distribution; LOCALIZATION; RASHBA; Science & Technology - Other Topics; Physics